RANCANG BANGUN APLIKASI MOBILE NOTIFIKASI BERBASIS ANDROID UNTUK MENDUKUNG KINERJA DI INSTANSI PEMERINTAHAN - Irsan, Muhammad (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
ABSTRACT: Employee performance ofgovernment agencies greatly effects their goodor bad service and the performance of theirwork. Surely any government agency willexpect all employees to perform well in theirwork. Within this paper, an application will bemade that is expected to help and support theirperformance. This application is functioned tosend notifications of information in real time, tomonitor, take action and to send an alertnotification to the desired employees and is alsoin realtime. Information sent is in the form ofannouncements of events, meetings, and otheractivities while monitoring, and warnings willbe made to employees from their work on thereport in order to complete the task on time andto employees that have a lot of work absencies.In addition, this application also has a functionthat allows the head office dispose of hissubordinates. This application uses GoogleCloud Messaging (GCM) to send notificationsof information and warnings. In order so thenotification and warning information is sent inreal time can be easily accessed, the applicationis made on Android-based mobile devices withthe information and warnings sent is done bythe Webservice-based application as anapplication server, so the notification andwarning information will be sent as soon asthere is internet connection. Based on testresults, the application is already running wellon android based mobile devices withinformation and warnings sent by the server caneither be sent in real time manually orautomatically.